1998
DOI: 10.1097/00007890-199802270-00019
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Decompensated Cirrhosis After Jejunoileal Bypass

Abstract: Patients undergoing liver transplantation for jejunoileal bypass-associated liver disease should, if possible, have their bypass reversed at the time of transplantation; otherwise, they must be followed closely and be biopsied routinely. Recurrent liver disease should prompt reversal of the jejunoileal bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Performing bariatric procedures prior to transplantation would be a possible strategy to cope with this emerging problem (23, 24). However, one must consider other side‐effects of bariatric surgery, such as development of non‐alcoholic steatohepatitis (NASH) and even cirrhosis of the liver (25, 26). In addition, changes in the absorption of immunosuppressive agents have been outlined in several publications (27–29).…”
Section: Discussionmentioning
confidence: 99%
“…Performing bariatric procedures prior to transplantation would be a possible strategy to cope with this emerging problem (23, 24). However, one must consider other side‐effects of bariatric surgery, such as development of non‐alcoholic steatohepatitis (NASH) and even cirrhosis of the liver (25, 26). In addition, changes in the absorption of immunosuppressive agents have been outlined in several publications (27–29).…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery may rarely lead to liver failure, especially after jejuno-ileal bypass and biliopancreatic diversion. Protein malnutrition and bacterial overgrowth are the main causes of liver damage following bariatric surgery (44). A recent systematic review analyzed 14 studies reporting 36 patients listed to LT after bariatric surgery.…”
Section: Lt In Bariatric Surgerymentioning
confidence: 99%
“…Historically BS procedures with a marked malabsorptive component, such as jejunoileal bypass (JIB) or BPD (Scopinaro procedure) were proven to cause severe life-threatening complications including acute liver failure in up to 10% of patient, and were therefore subsequently abandoned. 30 31 In a nationwide Belgian survey in 2010, 10 patients (nine of them with BPD and one JIB) were listed for LT due to severe liver failure after BS, with a median time of 5 years after the weight-loss surgical procedure. The authors concluded that, although rare, the BPD operation carries a potential risk of life-threatening liver failure.…”
Section: Progression Of Liver Fibrosis After Bs and Feasibility And Safety Of Bs In Patients With Cirrhosismentioning
confidence: 99%